The Antimicrobial Efficacy of Ethanolic Extract Obtained from Ficus benghalensis L. (Moraceae) Leaves - Tkachenko, Halyna; Buyun, Lyudmyla; Osadowski, Zbigniew; Honcharenko, Vitaliy; Prokopiv, Andriy (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
Medicinal plants have a great potential for providing novel drug leads with proven mechanism of action. The aim of our study was to investigate in vitro antimicrobial activity of ethanolic extract prepared from Ficus benghalensis L. leaves against Gram-positive (Staphylococcus aureus, methicillin-resistant Staphylococcus aureus locally isolated and Streptococcus pneumoniae) and Gram-negative bacterial strains (Klebsiella pneumoniae, Pseudomonas aeruginosa and Escherichia coli), as well as against fungus Candida albicans to determine the possible use of this plant in preventing infections. Antimicrobial activity of crude extract of the plant sample was evaluated by the paper disc diffusion method. Ethanolic extract obtained from leaves of Ficus benghalensis showed moderate antibacterial activity against Staphylococcus aureus, Escherichia coli, and Pseudomonas aeruginosa, while no significant antibacterial activity against Klebsiella pneumoniae and Streptococcus pneumoniae, methicillin-resistant S. aureus and Candida albicans was demonstrated. Among the tested microbial strains, bacteria were found to be more sensitive to many of the test agents than fungi. The antibacterial activity was more pronounced on the Gram-positive bacteria (Staphylococcus aureus) than the Gram-negative bacteria (Escherichia coli and Pseudomonas aeruginosa). The broad antibacterial activities of this extract could be as a result of the plant secondary metabolites (carbohydrates, reducing sugars, sterols, glycosides, phenolic compounds, tannins, saponins and flavonoids). Therefore, Ficus benghalensis has a great medicinal potential for the therapy of infections induced by Gram-positive and Gram-negative bacteria and may be used as a natural antiseptic and antimicrobial agent in medicine. Further investigation is necessary to identify those bioactive compounds, which will be a platform for clinical applications.